2020
DOI: 10.34085/buifd.702108
|View full text |Cite
|
Sign up to set email alerts
|

Kur’an Kursu Öğreticilerinin Meslekî Doyum Düzeyleri

Abstract: Yaygın eğitim kişilerin toplumsal değişimlere uyumunu sağlamak ve ulusal kalkınma hedeflerine ulaşmak için yaşam boyu eğitim felsefesi çerçevesinde yapılan tüm eğitim faaliyetleridir. Bunlar içinde yaygın din eğitimi resmi olarak Diyanet İşleri Başkanlığı eliyle yürütülen faaliyetlerdir. Özellikle yaygın din eğitimine katılan yetişkinlerin önemli bölümü kadınlardan ve bu eğitimi verenlerin de önemli kısmı kadın Kur'an kursu öğreticilerinden oluşmaktadır. Kur'an kursları aynı zamanda kadınların sosyalleşmesi iç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Experiencing professional burnout in certain occupational groups can be quite high compared to other occupational groups. This situation is quite common, especially in professions where there is face-to-face contact with people (Koç & Koç, 2020). In recent researches, many effects are mentioned, which cause teachers' professional burnout.…”
Section: Professional Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing professional burnout in certain occupational groups can be quite high compared to other occupational groups. This situation is quite common, especially in professions where there is face-to-face contact with people (Koç & Koç, 2020). In recent researches, many effects are mentioned, which cause teachers' professional burnout.…”
Section: Professional Burnoutmentioning
confidence: 99%
“…In the literature, although there is no study to determine the relationship between paternalist leadership and professional burnout, some results are indirectly similar to the findings obtained in this research. Various researches have revealed that the burnout status of the teachers decreases as they receive support from their principals (Yellice Yüksel et al, 2011), that the paternalist leadership positively affects the attitudes and behaviours of the employees (Köksal, 2011) and increases the job satisfaction of the employees (Uçar, 2019;Koç & Koç, 2020). Similarly, it has been shown that it helps employees to show voluntary behaviours (Gökdeniz et al, 2018) and reduces negative situations such as organizational exclusion (Akgün et al, 2019).…”
Section: The Relationship Between Paternalist Leadership Perceptions and Professional Burnout Levelsmentioning
confidence: 99%